A contribution to the millipede fauna of China: descriptions of four new species of the genus Nepalmatoiulus Mauriès, 1983 from high-altitude areas of Yunnan Province (Diplopoda, Julida, Julidae) - Mikhaljova, Elena V. (Zootaxa, 2023)
Four new species of the millipede genus Nepalmatoiulus Mauriès, 1983 (Julida, Julidae) are described from high-altitude areas of Yunnan Province in China: N. angustus sp. nov., N. arcuatus sp. nov., N. belousovi sp. nov. and N. kabaki sp. nov. A new faunistic record for the Laojunshan Mts. is given for N. emarginatus Mikhaljova, 2020. A brief overview of the Yunnan Nepalmatoiulus species is given. Taxonomic remarks are provided for nearly all new species.